(untitled) (Journal of Parents and Teachers, 1996)
Dialogue is essential to build relationships based on trust and respect, allowing active participation and listening. Manipulation and dogmatism prevent genuine communication, while the search for truth requires collaboration. Education should focus on shared experience and the development of a critical attitude.